Glanzmann’s thrombasthenia: a rare case presented with recurrent nasal bleeding - Kumbhar, Suhas G.; Swami, Shivling S.; Khapra, Kashvi (International Journal of Contemporary Pediatrics, 2023)
A rare congenital condition of platelet aggregation known as Glanzmann's thrombasthenia is caused by mutations in the Glycoprotein IIb or Glycoprotein IIIa gene, which leads to platelet malfunction. Glanzmann’s thrombasthenia is difficult to diagnose on basis of routine physical examination and is usually mis diagnosed because platelet morphology is normal as well as the platelet counts are in normal range, but bleeding duration is noticeably longer. The most prevalent signs of Glanzmann’s thrombasthenia include numerous types of bleeding, such as menorrhagia in females, recurrent nasal bleeding, mucocutaneous haemorrhage, continuous bleeding after injury or surgery, etc. Recurrent severe intractable causes of massive nasal epistaxis are relatively less common, particularly in cases where local causes do not explain the findings, then haematological causes should be suspected. Here we present a case of a 3 years old Indian boy who presented with recurrent massive epistaxis, fatigue, severe anaemia, and breathlessness who was diagnosed with Glanzmann’s thrombasthenia upon undergoing various investigations such as genetic testing and platelet assays. The patient was immediately started with supportive treatment and progress was made by the patient. Counselling was done to the patient’s family that it is a lifelong disorder and upon taking prescribed treatment bleeding episodes will be reduced. Overall Glanzmann’s thrombasthenia is a lifelong disorder which is difficult to diagnose, and misdiagnosis is very common regarding this disease, hence the clinician should remain alert regarding this rare congenital disorder and appropriate lab investigations should be done and treatment must be started in due time.